EVALUASI RENDAHNYA TINGKAT KELULUSAN PELATIHAN PENGADAAN BARANG/JASA MENGGUNAKAN MODEL PEMBELAJARAN BENDED LEARNING DI BADAN PENGEMBANGAN SUMBER DAYA MANUSIA PROVINSI JAWA BARAT - Sujatmoko, Sujatmoko; Dipl.W.R , Dipl.W.R (Media Bina Ilmiah, 2024)
The low graduation rate for goods/services procurement training participants at the West Java Province Human Resources Development Agency (BPSDM) is a serious problem in implementing the Blended Learning model. This problem is related to the formulation of Learning concepts, curriculum planning, teaching strategies, teaching materials, resources used, comprehensive evaluation, and measuring Learning outcomes. Data shows that the graduation percentage of training participants is still low. This research was conducted to evaluate Learning models and identify factors that influence low graduation rates using a qualitative descriptive approach. Evaluation focuses on four main aspects: Context Evaluation, Input Evaluation, Process Evaluation, and Product Evaluation. The aim of this research is to gain an in-depth understanding of the evaluation of the Blended Learning Learning model in goods/services procurement training, so that it can provide effective recommendations for dealing with the problems faced. The research results show that although some aspects of the training were successful, the low graduation rate of participants indicates significant challenges that need to be overcome. Concrete steps are needed to increase the effectiveness of training, including increasing the relevance of the material, more comprehensive initial training, special support for participants who experience difficulties, as well as innovations in teaching methods that can better motivate participants. In this way, it is hoped that the graduation rate and benefits of the Blended Learning model can be further optimized.